English Teaching in an Indonesian Vocational High School Majoring Industrial Machinery Engineering - Muhammad Natsir; Anwar Soleh Purba; Ellyana Ellyana; Anggraini Thesisia Saragih; Bakhrul Khair Amal (AL-ISHLAH: Jurnal Pendidikan, 2022)
Theoretically, teaching English in Vocational High Schools (VHS) should relate to and support specific skills required by students based on their major. In reality, teaching English in Indonesian VHS is mostly similar to general schools. Discussions on this issue have been long contested by many researchers in diverse contexts, yet, little focus was given to the Industrial Machinery Engineering major. Therefore, the present study aims to investigate the actual needs of students in industrial machinery engineering in learning English. By administering questionnaires to 200 students at a VHS in Medan, this mixed-method study seeks the students' comprehension of the types of English language skills they used, the purpose of learning these skills, their ability to use the skills, and the basic English language skill they must acquire as part of their English language course arrangement. To scrutinize deeper investigation, in depth-interviews were also employed with ten students in that school. The findings emphasize several aspects that students of English for industrial machinery engineering require in learning English and establish the students’ English language skills gaps, wants, and needs. This paper also provides pedagogical implications that could aid in improving English language teaching tailored to the needs of the students.